Risk of preterm birth in relation to history of preterm birth: a population‐based registry study of 213 335 women in Norway. (28th November 2021) - Tingleff, T; Vikanes, Å; Räisänen, S; Sandvik, L; Murzakanova, G; Laine, K
Abstract : Objective: To assess the association between preterm first birth and preterm second birth according to gestational age and to determine the role of placental disorder in recurrent preterm birth. Design: Population‐based registry study. Setting: Medical Birth Registry of Norway and Statistics Norway. Population: Women ( n  = 213 335) who gave birth to their first and second singleton child during 1999–2014 (total n  = 426 670 births). Methods: Multivariate logistic regression analyses, adjusted for placental disorders, maternal, obstetric and socio‐economic factors. Main outcome measures: Extremely preterm (<28 +0  weeks), very preterm (28 +0 –33 +6  weeks) and late preterm (34 +0 –36 +6  weeks) second birth. Results: Preterm birth (<37 weeks) rates were 5.6% for first births and 3.7% for second births. Extremely preterm second births (0.2%) occurred most frequently among women with an extremely preterm first birth (aOR 12.90, 95% CI 7.47–22.29). Very preterm second births (0.7%) occurred most frequently after an extremely preterm birth (aOR 12.98, 95% CI 9.59–17.58). Late preterm second births (2.8%) occurred most frequently after a previous very preterm birth (aOR 6.86, 95% CI 6.11–7.70). Placental disorders contributed 30–40% of recurrent extremely and very preterm births and 10–20% of recurrent late preterm birth. Conclusion: A previous preterm first birth was a major risk factor for a preterm second birth. The contribution of placental disorders was more pronounced for recurrent extremely and very preterm birth than for recurrent late preterm birth. Among women with any category of preterm first birth, more than one in six also had a preterm second birth (17.4%). Tweetable abstract: Preterm first birth is a major risk factor for subsequent preterm birth, regardless of maternal, obstetric or fetal risk factors. Tweetable abstract: Preterm first birth is a major risk factor for subsequent preterm birth, regardless of maternal, obstetric or fetal risk factors. This article includes Author Insights, a video abstract available at: https://vimeo.com/bjog/authorinsights17013